Legal Jurisprudential Analysis of Some Causes of Exemption from Civil Liability in the Qur'an - Hossein Houshmand Firuzabadi; Meysam Khazaei; Hossein Javar; Ayyūb Amraei (آموزه‌‌های فقه مدني)
On the basis of respect for the dignity of persons, any invasion on the body (physical) integrity, psychological (moral) status and property and abandoning of persons is prohibited, and in principle, any kind of damage, both (physical) integrity and psychological (moral), in the realm of property and persons is subject to a state of guarantee. No one has the right to damage others, and in case of damage, the person is obliged to compensate the damage. At the same time, there are cases in which, if occurred, the civil liability of the doer of damage is removed and the person is exempted from compensation for damages, which may be due to the justifiable causes (lawful excuse) of the harmful act or the causations of exemption from civil liability. There are several titles in the Qur'an that indicate exemption from responsibility. These include lawful defense, the applicable of the right, the proof of the right and litigation, bona fide (good faith), and the application of punishment. Based on the analysis of the relevant verses, it seems that the decline of the element of respect in each of the above-mentioned titles (directly or indirectly) and the disruption of the occurrence of the “subject of guarantee” is the justifying factor of the harmful act and the cause for exemption from civil liability and the majority of cases, as a particularized from the terms of the guarantee, agree with the legal analysis.